The biogeography of gastrointestinal mucosal microbiota of beef cattle at harvest - Young, J. Daniel; Pinnell, Lee J.; Wolfe, Cory A.; Doster, Enrique; Valeris-Chacin, Robert; Lawrence, Ty E.; Richeson, John T.; Morley, Paul S. (Frontiers in Microbiology, 2024)
IntroductionThe gastrointestinal microbiota profoundly influences the health and productivity of animals. This study aimed to characterize microbial community structures of the mouth, gastrointestinal tract (GIT), and feces of cattle.MethodsSamples were collected from 18 Akaushi crossbred steers at harvest from multiple locations, including the oral cavity, rumen, abomasum, duodenum, jejunum, ileum, cecum, spiral colon, distal colon, and feces. These cattle were raised without exposure to antimicrobial drugs or hormone implants. Total microbial abundance was assessed using qPCR targeting the V3–V4 region of the 16S rRNA gene, and microbial community composition was evaluated through 16S rRNA gene sequencing.ResultsTotal microbial abundance was lesser in the small intestine than in other GIT regions (p ≤ 0.05). Additionally, microbial communities in the small intestine had lower richness and diversity than other regions (p ≤ 0.05). Microbial community compositions were measurably different along the GIT, with greater relatedness in adjacent GIT sections when progressing from oral to aboral locations. Firmicutes, Bacteroidota, and Actinobacteria were the dominant phyla in all samples. However, variations in composition were evident at lower taxonomic levels within these dominant phyla among samples from different regions. Genera previously associated with healthy gut microbiome communities were observed in low abundance across GIT regions. Taxa historically associated with liver abscesses (e.g., Fusobacterium and Trueperella) were detected in low abundance (≤0.02% relative abundance) throughout the GIT. In contrast, Bacteroides, which recently has been identified as a dominant feature in many liver abscesses, was observed in greater relative abundance (5.2% on average) in the hindgut.DiscussionThis study provides an in-depth evaluation of the GIT of harvest-ready Akaushi crossbred cattle of varying growth rates. Clear differences exist in the abundance and composition of microbial populations at different points of the GIT. Unfortunately, no single GIT location can adequately represent the microbial communities of the entire GIT, which has important implications for future research. Additionally, examining microbiome data only at the phylum level likely oversimplifies important complexities of the microbial community structures, and investigations of lower taxonomic ranks should be included.